The Interior Space Aesthetics of Al Aqsa Manarat Qudus Mosque: Analysis of Space-Forming Elements - Sela Agustin Eka Nila (Journal Of Architectural Design & Technology, 2025)
Abstract: The Al-Aqsa Manarat Qudus Mosque is the oldest mosque on the island of Java. The presence of the paduraksa gate inside the mosque, specifically in the main building of the main prayer hall, is what makes this mosque unique. The problem addressed in this study is how to understand the beauty of the Al-Aqsa Manarat Qudus Mosque from the perspective of Djelantik's theory of beauty. This method is a study aimed at dissecting the characteristics of beauty in a work of art using aesthetic theory. The data used were obtained from field studies, literature studies, and interviews. The method employed is a qualitative descriptive method with a single embedded case study. The results of this research indicate that the interior of Al-Aqsa Manarat Qudus Mosque has characteristics of beauty from an aesthetic perspective. Beauty is identified through the description of the composition of shapes, principles, elements, and meanings in the mosque's interior. Al-Aqsa Manarat Qudus Mosque has a strong sense of unity, viewed from the traits of symmetry, rhythm, and harmony present in its interior. The spatial elements in the Al-Aqsa Manarat Qudus Mosque have geometric shapes, smooth textures, and soft colors. This creates a solemn and grand atmosphere in the Al-Aqsa Manarat Qudus Mosque.